Relationship between psychological well-being and job satisfaction of nurses in selected public hospitals in Manila - Melicor, Mary Joy E. 4 0 16; 5 (2018)
ABSTRACT: Psychological well-being is how people evaluate their lives, these evaluations are may be in the form of cognitive or affective that can affect your job satisfaction. This study profiles the psychological well-being and job satisfaction of nurses. A descriptive method was utilized and survey technique was used for gathering data with the aimed to determine the relationship between the psychological well-being and job satisfaction of nurses in selected public hospitals in Manila. A purposive sampling was used with the 3 qualifications to gather a total of 100 nurse respondents in public hospitals. A questionnaire that assessed the frequency distribution of their psychological well-being and job satisfaction. Frequency distribution, mean and standard deviation was used to describe the scores gathered from the respondents, while Pearson Correlation was used to test the significance correlation of the variables. Due to rejection of null hypothesis, some recommendation was proposed.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2